Enhanced mobility of Cu4SnS4 films prepared by annealing SnS–CuS stacks in a graphite box. (October 2017) - Chalapathi, U.; Poornaprakash, B.; Park, Si-Hyun
Highlights: Preparation of Cu4 SnS4 films by annealing chemically grown SnS–CuS stacks. Effect of annealing temperature on Cu4 SnS4 films is investigated. Films exhibited good grain growth and morphology on annealing at 550 and 580 °C. Films prepared at 550 and 580 °C exhibited a higher hole mobility of 150 cm 2 V −1 s −1 . Abstract: High-quality Cu4 SnS4 thin films are prepared by annealing chemical bath-deposited SnS–CuS stacks in a graphite box. The effects of annealing temperature on the grain growth and morphology of these films are investigated in this study. Results showed that the films prepared at 500–580 °C yielded an orthorhombic crystal structure with lattice parameters a  = 1.371 nm, b  = 0.766 nm and c  = 0.643 nm, a crystallite size of 260 nm, an increased grain size from 2 μm to greater than 6 μm, a direct optical band gap of 1.0 eV, and p-type electrical conductivity. The films prepared at 550 °C and 580 °C exhibited a relatively high hole mobility of 150 cm 2 V −1 s −1 . These properties suggest that the films developed in this study can yield reasonable device efficiency when used as solar cell absorber layers.